Gitar Tunggal Lampung: Enculturation and Ethnopedagogy in Advancing Formal Music Education (Universitas Negeri Semarang, 2023)
Formal music education often uses systematic teaching methods, a planned curriculum, leveling, organization, and standardized learning stages. From a pedagogical perspective, learning music provides a more imaginative, improvisatory learning structure besides all these standard rules. By capturing the social practice of music in the community, music scholars can enrich their academic experience and ideas about designing informal music learning in the classroom. The gitar tunggal players from Lampung may serve as ideas for those learning music formally. While they lack musical and academic literacy, they also provide useful self-learning concepts. Over the past four years, data for this study were gathered using ethnomusicological methods. Online databases were used in addition to the primary data collected through fieldwork. When designing curricula, music scholars might include the ideas of enculturation and Ethno pedagogy. A useful suggestion for enhancing formal music education is to base instruction on local culture and learn it from vernacular musicians in Lampung.